PWE-156 Post-oesophagectomy diaphragmatic hernias: an increasing problem with the move to minimally invasive oesophagectomy. (22nd June 2015) - Matthews, J; Bhanderi, S; Mitchell, H; Vohra, R; Griffiths, EA
Abstract : Introduction: Post-oesophagectomy diaphragmatic hernias (PODHs) are serious complications following oesophagectomy. However, the incidence of PODHs are unknown. The aim of this study was to describe and compare the incidence of PODHs over time and analyse the outcomes of patients who develop a PODH. Method: A prospective database of all oesophagectomies performed for cancer between 2001 to 2014 was analysed. Patients diagnosed with PODH were identified and data extracted regarding demographics, details of oesophagectomy, pathology, PODH symptoms, diagnosis and treatment. Results: A total of 507 transthoracic oesophagectomies were carried out between 2001 and 2014. Overall, 21 patients (18 males and 3 females) developed PODH. The incidence of PODH after open 2 or 3 stage oesophagectomy was 3/221 (1.3%) compared to 14/212 (6.6%) following laparoscopic hybrid oesophagectomy and 4/68 (5.9%) following minimally invasive oesophagectomy (MIO). Median age was 63 (range 55 to 82) years. 17 (81%) had surgery for lower oesophageal or gastro-oesophageal junctional adenocarcinoma. Of those who developed a PODH, 10 (48%) patients presented as an emergency and 11 (52%) patients with outpatient symptoms. Common presenting symptoms were shortness of breath, chest pain, vomiting and cough. Five (24%) patients develop PODH within 7 days of the index surgery, a further 3 (14%) within 90 days, 8 (38%) at 2 years and 4 (24%) at 5 years. Twenty patients had corrective surgery for PODH with hiatal suture repair (n = 15), hiatal mesh repair (n = 2), and other surgical procedures (n = 3). These were performed either laparoscopically (n = 15) or as open repairs (n = 5). However, 4 patients required conversation. Median length of stay was 12 days (range 3 to 48 days); but shorter when successfully treated laparoscopically. Thirty day post-operative mortality was 10% (n = 2) and 20% (n = 4) recurred requiring further surgery. Conclusion: PODH is a common complication following hybrid oesophagectomy and MIO. One hypothesis is there is less intra-abdominal adhesions formed when minimal access techniques are used. Careful thought is needed to identify surgical techniques to prevent PODH forming when minimal access oesophagectomy are performed. Disclosure of interest: None Declared.